Application of EVA concept in business "SBB" limited liability company Belgrade - Bešlić-Obradović Dragana; Bešlić-Rupić Ivana (Trendovi u Poslovanju)
The contemporary business environment has imposed the need to continuously find and define new concepts and tools that support the strategic management of a company. Among them, Economic Value Added - EVA is considered as the essential principle for the evaluation of company performance in terms of shareholder return. EVA is taxable profit less the total cost of capital (borrowed and owned). The contribution of the EVA concept is reflected by looking at economic rather than accounting profits. This concept was adopted by many companies in Serbia, among which is also "SBB" limited liability company - Belgrade.